SOME QUESTIONS ABOUT THE FUNCTION OF THE TEACHER OF THE RUSSIAN LANGUAGE IN THE UZBEAN SCHOOL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the issues of organic inclusion in the system of the educational process of new technologies, to develop and justify the technology of using innovative forms of instruction in the Russian language in an Uzbek school.